2005
DOI: 10.1111/j.1939-1676.2005.tb02754.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Output Measurement by Partial Carbon Dioxide Rebreathing, 2-Dimensional Echocardiography, and Lithium-Dilution Method in Anesthetized Neonatal Foals

Abstract: The objective of this study was to assess 2 noninvasive methods of measuring cardiac output (CO) in neonatal foals by comparing results to that of the lithium-dilution method. Ten neonatal foals were anesthetized and CO was manipulated by varying the depth of anesthesia and infusion of dobutamine. Concurrent CO measurements were obtained by lithium dilution (reference method), partial carbon dioxide (CO 2 ) rebreathing, volumetric echocardiography (cubic, Teichholz, Bullet, area-length, and single and biplane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 47 publications
(11 reference statements)
3
28
0
Order By: Relevance
“…Other authors have determined that UDCO compared favorably with pulmonary thermodilution 17 and aortic flow‐probe models 14,25 in mice, rats, and humans 14,17,26 . The mean bias and relative bias of the current study was similar to that reported with other methods evaluating CO in foals: trans‐thoracic echocardiogram versus LiDCO (−4.2±20.9%), 11 partial carbon dioxide rebreathing versus LiDCO (−17.3±57 mL/kg/min) 2 and pulmonary thermodilution versus LiDCO (47.5±49.2±mL/kg/min) 5 . It is widely accepted that calculation of bias and precision represents the best statistical method of comparing 2 techniques measuring the same physiological variable, such as CO.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Other authors have determined that UDCO compared favorably with pulmonary thermodilution 17 and aortic flow‐probe models 14,25 in mice, rats, and humans 14,17,26 . The mean bias and relative bias of the current study was similar to that reported with other methods evaluating CO in foals: trans‐thoracic echocardiogram versus LiDCO (−4.2±20.9%), 11 partial carbon dioxide rebreathing versus LiDCO (−17.3±57 mL/kg/min) 2 and pulmonary thermodilution versus LiDCO (47.5±49.2±mL/kg/min) 5 . It is widely accepted that calculation of bias and precision represents the best statistical method of comparing 2 techniques measuring the same physiological variable, such as CO.…”
Section: Discussionsupporting
confidence: 76%
“…It is widely accepted that calculation of bias and precision represents the best statistical method of comparing 2 techniques measuring the same physiological variable, such as CO. However, a review of the current literature assessing CO methodologies has revealed a notable lack of consistency regarding the criteria used to determine whether a newer technique can replace or be used interchangeably with an older or more established method 11 . It was demonstrated that by combining the errors of both the test and reference method that acceptance of a new method of measuring CO should rely on limits of agreement of up to approximately ±30% 27 .…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…; Giguère et al. ). The technique might show higher variability than transoesophageal measurement because parallel alignment between ultrasound beam and aortic blood flow is more difficult (Young et al.…”
Section: Discussionmentioning
confidence: 96%